Alotrasplante tubo-ovárico como "unidad anatomo-funcional" en la coneja - Martínez Meraz, Manuel (Universidad Autónoma Metropolitana, 2007)
The aim of this study was to re-establish the endocrine and reproductive function in tubal-ovariectomized rabbits using orthotopic tubal-ovary allotransplants as the “anatomical-functional unit” with a vascular microsurgical technique. Fifty-five White New Zeland, non-consanguineous rabbits and 6 confirmed-fertile males were used. The rabbits were divided into 5 experimental groups: group A (n=20) was comprised by donors submitted to right salpingo-oophorectomy which served as the donated allo-graft followed by hysterectomy plus left salpingooophorectomy and euthanasia. To control group 1 (n=10) no cyclosporin (CsA) was administered and was submitted to left salpingo-oophorectomy (SOI). Group 2 (n=10) was the allotransplant group and did not receive CsA. They were submitted to bilateral salpingo-oophorectomy, followed by orthotopic right tubalovarian allotransplant. 10 mg/kg/day of CsA was administered to rabbits for the first 21 days, and 5 mg/kg/day for the rest of the study. Control group 4 (n=5) received CsA just as group 3 and were submitted to left salpingo-oophorectomy. During the study the following parameters were measured: permeability of the tubal and vascular anastomosis, estradiol (E2), progesterone (P4), folliclestimulating hormone (FSH) and luteinizing hormone (LH), number of babies per litter, degree of adherences, istopathological study of the uteri, Fallopian tubes and ovaries. The results showed that there was immediate permeability of the tubal anastomosis in 100% of the cases and a late permeability of 15%. Immediate permeability of the vascular anastomosis was 92.5%, while late permeability was 16.6%. Serum E2, P4, FSH and LH levels were measured at the start of the study (baseline), during the second, sixth and tenth week after surgery. Groups 1, 3 and 4 showed a significant increase in serum E2 and P4 levels corresponding to the second week of gestation, compared to the group 2 hormone levels (p < 0.05). Group 2 showed a significant increase in serum LH and FSH levels during week 10, compared to the serum LH and FSH levels of groups 1, 3 and 4 (p < 0.05). In group 1 (control group) 87.5% of the rabbits were gestating. With the administration of CsA, all of the rabbits in group 4 (control) became pregnant. In group 2, provided the allotransplant without the administration of CsA, all of the rabbits rejected the allotransplant and none became pregnant. In group 3, provided the allotransplant and CsA, three rabbits (37.5%) did not reject the allotransplant, one rabbit became pregnant corresponding to 12.5 % of the animals and in two rabbits the endocrine function was re-established (37.5%). It can be concluded that the tubal-ovarian allotransplant as an “anatomicalfunctional unit”, together with the administration of CsA, re-establishes endocrine function in 37.5% of the cases, while in 12.5% of the cases, fertility was reestablished.; l objetivo de este estudio fue evaluar la función endocrina y reproductiva de conejas tubo-ovariectomizadas con alotrasplante tubo-ovárico ortotópico como “unidad anatomo-funcional”, empleando una técnica de microcirugía vascular. Se utilizaron 55 conejas Nueva Zelanda Blancas (NZB), no consanguíneas y 6 machos de fertilidad probada. Las conejas se dividieron en 5 grupos experimentales: El grupo A (n=20) donadoras, se les efectuó salpingooforectomía derecha, que fue el aloinjerto donado, seguida de histerectomía más salpingooforectomía izquierda y eutanasia. El grupo 1 (n=10) Control sin la administración de ciclosporina (CsA), a las que se les realizó salpingooforectomía izquierda (SOI). El grupo 2 (n=10) alotrasplante sin la administración de CsA, se les efectuó salpingooforectomía bilateral (SOB), seguida de alotrasplante tuboovárico derecho, ortotópico. El grupo 3 (n=10) Alotrasplante con la administración de CsA, se les realizó salpingooforectomía bilateral, seguida de alotrasplante tubo-ovárico derecho, ortotópico. A las conejas se les administró CsA 10 mg/kg/día durante los primeros 21 días, para continuar con 5 mg/Kg/día durante el resto del estudio. El grupo 4 (n=5) Control con la administración de CsA, a las que se les realizó salpingooforectomía izquierda y se les administró CsA, con el mismo esquema que al grupo 3. Durante el estudio se determinaron los siguientes parámetros: permeabilidad de la anastomosis tubaria y vascular; niveles séricos de estradiol (E2), progesterona (P4), hormona folículo estimulante (FSH) y hormona luteinizante (LH); fertilidad, número de crías por camada, grado de adherencias, estudio histopatológico de úteros, trompa de Falopio y ovario. Los resultados mostraron que hubo permeabilidad inmediata de las anastomosis tubarias en el 100% de los casos y una permeabilidad tardía en el 15%. La permeabilidad inmediata de las anastomosis vasculares fue del 92.5% mientras que la tardía fue del 16.6%. Se determinaron los niveles séricos de E2, P4, FSH y LH al inicio del experimento (basal), a la 2ª, 6ª y 10ª semanas después de la cirugía. Los resultados en los grupos 1, 3 y 4, mostraron un incremento significativo en los niveles séricos de E2, P4, en la 6ª semana, que correspondieron a la segunda semana de gestación, comparados con los niveles de las hormonas del grupo 2 (p< 0.05). En el grupo 2, hubo un incremento significativo en los niveles séricos de LH y FSH en la semana 10, comparado con los niveles de LH y FSH de los grupos 1, 3 y 4 (p < 0.05). En el grupo 1, control, sin la administración de CsA, el 87.5% de las conejas quedaron gestantes. En el grupo 4, control, con la administración de CsA, todas las conejas, quedaron gestantes. En el grupo 2, de alotrasplante sin la administración de CsA, todas las conejas, presentaron rechazo al aloinjerto y ninguna coneja quedo gestante. En el grupo 3, de alotrasplante con la administración de CsA, tres conejas (37.5%) no presentaron rechazo, solamente una coneja resultó gestante, lo que correspondió al 12.5% de los animales, y en dos conejas más se restableció la función endocrina (37.5%). Se puede concluir que el alotrasplante tubo-ovárico como "unidad anatomofuncional", con la administración de CsA, restableció la función endocrina en el 37.5% de los casos y en el 12.5% restableció la fertilidad.